Computing for Comparative Microbial Genomics - Braverman, Mark (Springer, 2017)
Among all computer-generated mathematical images, Julia sets of rational maps occupy one of the most prominent positions. Their beauty and complexity can be fascinating. They also hold a deep mathematical content.